2019
DOI: 10.1002/jcp.28181
|View full text |Cite
|
Sign up to set email alerts
|

Immune therapy of melanoma: Overview of therapeutic vaccines

Abstract: Melanoma is the most serious type of skin cancer which develops from the occurrence of genetic mutations in the melanocytes. Based on the features of melanoma tumors such as location, genetic profile and stage, there are several therapeutic strategies including surgery, chemotherapy, and radiotherapy. However, because of the appearance resistance mechanisms, the efficiency of these treatments strategies may be reduced. It has been demonstrated that therapeutic monoclonal antibodies can improve the efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 89 publications
0
24
0
3
Order By: Relevance
“…It has been suggested that breast cancer cells have different pathologic characteristics, which enable them to react differently to different medications (C. I. Li, Uribe, & Daling, 2005). Studies have shown that harboring mutations in cell signaling pathways, such as transforming growth factor‐β (TGF‐β), Wnt/β‐catenin, phosphoinositide 3‐kinase/protein kinase (PI3K/AKT), nuclear factor‐κB (NF‐κB), and other signaling pathways gives cancer cells different characteristics and malignant potentials (Payandeh et al, 2019). Furthermore, different specimens of breast cancer have different gene expression profiles, and it has been suggested that having differences in master regulators of signaling pathways and gene translation could underlie this heterogeneity (Malhotra, Zhao, Band, & Band, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that breast cancer cells have different pathologic characteristics, which enable them to react differently to different medications (C. I. Li, Uribe, & Daling, 2005). Studies have shown that harboring mutations in cell signaling pathways, such as transforming growth factor‐β (TGF‐β), Wnt/β‐catenin, phosphoinositide 3‐kinase/protein kinase (PI3K/AKT), nuclear factor‐κB (NF‐κB), and other signaling pathways gives cancer cells different characteristics and malignant potentials (Payandeh et al, 2019). Furthermore, different specimens of breast cancer have different gene expression profiles, and it has been suggested that having differences in master regulators of signaling pathways and gene translation could underlie this heterogeneity (Malhotra, Zhao, Band, & Band, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Arising evidence suggests that miRNAs are involved in various pathways. Studies exhibited various functions of specific miRNAs in different cancers as well as breast cancer (Hrdlickova, de Almeida, Borek, & Withoff, ; Mulrane, Klinger, McGee, Gallagher, & O'Connor, ; Payandeh et al, ). MiRNAs play different roles in diverse mechanisms and signaling pathways in breast cancer and repress protein (Tarhriz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos recentes mostraram que baixos níveis de oxigênio (hipóxia) podem ser essenciais para a transformação dos melanócitos (16), e que a MEC, condicionada por células agressivas de melanoma, pode transformar epigeneticamente os melanócitos normais em direção a um fenótipo de melanoma mais invasivo (17). (27,28).…”
Section: Melanoma: Características Epidemiologia E Tratamentounclassified
“…Atualmente, a imunoterapia ou o uso de anticorpos monoclonais tem sido utilizado para melhorar a eficácia destas terapias para o melanoma (27). Nesse contexto, uma estratégia terapêutica promissora que tem se destacado no tratamento do melanoma é o uso de anticorpos que bloqueiam receptores de checkpoints imunes como CTLA-4 (cytotoxic T-lymphocyte-associated antigen 4) e PD-1 (programmed cell death 1) (27).…”
Section: Melanoma: Características Epidemiologia E Tratamentounclassified
See 1 more Smart Citation